Pengaruh Penggunaan E-Wallet Terhadap Pengeluaran Mahasiswa Universitas 17 Agustus 1945 Surabaya - Tri Hutomo Yogiantoro (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to analyze the impact of e-wallet usage on the spending patterns of students at Universitas 17 Agustus 1945 Surabaya. The development of digital financial technology has altered consumption behavior among the public, particularly students. The convenience of transactions and the various promotions offered by e-wallets are believed to drive an uncontrolled increase in student spending. Focusing on students at Untag Surabaya as the specific subject, this study employs a simple quantitative approach that reflects the students' actual circumstances. Data were collected via student questionnaires and analyzed using simple linear regression. The results indicate that e-wallet usage has a positive and significant impact on student spending; higher e-wallet usage correlates with a greater tendency for increased spending. These findings highlight the importance of financial literacy in the use of digital technology.